STUDI PERUBAHAN HUTAN MANGROVE DI PANTAI AIA BANGIH KECAMATAN SUNGAI BEREMAS KABUPATEN PASAMAN BARAT - Rapi’ah, Rapi’ah; Hermon, Dedi; Erita, Yenni (Pendidikan Geografi, 2013)
Indonesia is a country that have a very large coastal areas, because Indonesia is an archipelagic country with tired coastline as long as 81.000 km. Besides occupying large region, coastal areas consist of various supporter ecosystems like ecosystem of mangrove forest. Then access for coastal area of disposed improve exploiting rate of coastal area in the next years. Although in exploiting of economic resource accounting and also exploiting of room. Besides, something else which may not be disregarded is a fact that indicate not less than 60% resident of Aia Bangih live in coastal area.The aim of this research is to know (1). Mangrove forest alteration in Aia Bangih beach in 2002 (2). Mangrove forest alteration in Aia Bangih beach in 2012 (3). Mangrove forest alteration in Aia Bangih beach in 2002 until 2012 that happened in Aia Bangih Beach District Of Sungai Baremas Sub-Province West Pasaman. The kinds of this Research is descriptive research. With aim to describe what there in this time, make a note, analysis and interpret the condition of which is happened now or in the last. This Research area is in coastal region of Aia Bangih Diatrict Of Sungai Beremas Sub-Province West Pasaman.The data analyses technique used to know mangrove forest alteration that happenad in research location with steps (1). Interpretation into two maps is mangrove forest alteration map in 2002, and Mangrove forest alteration map in 2012 with Arc View 3.3 (2). Overlay mangrove forest alteration map by analyses tool Arc View 3.3 (3). To know mangrove forest alteration in Aia Bangih Beach District Of Sungai Beremas Sub-Province West Pasaman with GIS Arc View3.3.